Smart secure systems – IoT and Analytics Perspective : second International Conference on Intelligent Information Technologies, ICIIT 2017, Chennai, India, December 20-22, 2017, Proceedings /: second International Conference on Intelligent Information Technologies, ICIIT 2017, Chennai, India, December 20-22, 2017, Proceedings. (2018) - Unknown
No abstract available